2022
DOI: 10.1590/1414-431x2021e11631
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the current available treatment for COVID-19 and the impact of antibiotic administration during the pandemic

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has caused several problems in healthcare systems around the world, as to date, there is no effective and specific treatment against all forms of COVID-19. Currently, drugs with therapeutic potential are being tested, including antiviral, anti-inflammatory, anti-malarial, immunotherapy, and antibiotics. Although antibiotics have no direct effect on viral infections, they are often used against secondary bacterial infections, or even as empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
(99 reference statements)
0
3
0
2
Order By: Relevance
“…), puesto que, al ser una enfermedad nueva, se la ha tratado empíricamente según las necesidades del paciente (13) (17). A pesar de que, la Organización Mundial de la Salud (OMS) no recomienda el uso de antibióticos en pacientes con COVID-19 leve a moderado (18), en esta investigación se destaca el uso intensivo de este grupo de fármacos (100 %), siendo el más común la ceftriaxona (cefalosporina de tercera generación) y la levofloxacina (fluoroquinolona). En Ecuador el uso de ceftriaxona está limitado debido a la 5.…”
Section: Discussionunclassified
“…), puesto que, al ser una enfermedad nueva, se la ha tratado empíricamente según las necesidades del paciente (13) (17). A pesar de que, la Organización Mundial de la Salud (OMS) no recomienda el uso de antibióticos en pacientes con COVID-19 leve a moderado (18), en esta investigación se destaca el uso intensivo de este grupo de fármacos (100 %), siendo el más común la ceftriaxona (cefalosporina de tercera generación) y la levofloxacina (fluoroquinolona). En Ecuador el uso de ceftriaxona está limitado debido a la 5.…”
Section: Discussionunclassified
“…Previous research reported that deceased COVID-19 patients were more likely to have received antibiotics (84.6% vs 75.9%). 13,14 Another study of 81 patients with COVID-19 reported that an elevated neutrophil-to-lymphocyte ratio (>9.8) was related to acute respiratory distress syndrome (ARDS) and was also related to receipt of non-mechanical and mechanical ventilation. 15 An increased D-dimer level is an indication of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun tidak memiliki efek langsung pada infeksi virus, antibiotik sering digunakan untuk menangani infeksi bakteri sekunder, atau bahkan sebagai pengobatan empiris untuk mengurangi viral load, infeksi, dan replikasi virus corona. Terdapat banyak kekhawatiran tentang pendekatan terapeutik ini karena dapat mempercepat dan/atau meningkatkan tingkat resistensi antibiotik jangka panjang (Paula et al, 2022). Meskipun insiden rendah (8%) dari koinfeksi yang dilaporkan diantara pasien dengan Covid-19, 72% pasien menerima terapi antibiotik (Rawson et al, 2020) Antibiotik yang paling banyak diresepkan adalah levofloxacin i.v dengan persentase 35,59% dan antibiotik kedua terbanyak adalah ceftriakson i.v sebesar 30,35%.…”
Section: Hasilunclassified